Effect of maturation stage on the physical, chemical and biochemical composition of black mulberry (Research, Society and Development, 2020)
This work aimed to evaluate the physical, chemical and biochemical characteristics of black mulberry (Morus nigra L.) cultivated in Lavras, Minas Gerais, Brazil, at different maturation stages. The fruits were harvested and separated into five different stages according to the color of the surface. Afterwards, the fruits were submitted to the physical and chemical analyses and analysis of pectin methylesterase and polygalacturonase activity. With the advancement in maturation stages of black mulberry, it was possible to observe chlorophyll degradation with concomitant anthocyanin synthesis. There was an increase in soluble solids contents, sugars and pH, decrease of total acidity and respiratory rate as well as decrease of total pectin and increase of the soluble pectin. Furthermore an increase of the activity of the enzymes pectin methylesterase and polygalacturonase and the consequent softening of the fruits was also noted.